THE BASIC PRINCIPLES OF THE IDEAL ISLAMIC SOCIETY (KHAIR UMMAH) IN MAINTAINING RELIGIOUS SOLIDARITY IN THE ISLAMIC WORLD. - Abdul Syukur; Muhajir; Eko Subroto (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
Abstract Every Muslim is obliged to invite others to the good and forbid them from bad deeds. In the Qur'an, Allah SWT mentions the characteristics of khairu ummah. Khairu ummah can be a glorious achievement for Muslims as illustrated in the verse of Allah above if the characteristics of khairu ummah are fulfilled. There are at least three characteristics that must be fulfilled, namely amar ma'ruf, nahi mungkar, and faith in Allah. This research uses a qualitative research approach based on its characteristics with the category of library research.